Comparison of multiplex syndromic panel tests with conventional methods in the detection of gastroenteritis agents - Özlem Aydemir; Hande Toptan; Elif Ö Şahin; Hüseyin A Terzi; Gökçen Ormanoğlu; Mehmet Köroğlu; Mustafa Altındiş (Journal of Infection in Developing Countries)
Introduction: We aimed to evaluate the performance of multiplex polymerase chain reaction (PCR)-based FTD gastroenteritis kit (Fast-Track Diagnostics, Esch-sur-Alzette, Luxembourg) and QIAstat-Dx gastrointestinal panel (Q-GP; Hilden, Germany) in the detection of different enteric pathogens.